Theoretical and Empirical Analysis of the New Payroll Tax Scheme: Improving Efficiency and Compliance in Indonesia - Hidayati, Mainita; Arianty, Fitria (Jurnal Vokasi Indonesia, 2026)
The potential for tax revenue from Payroll Tax in Indonesia can still be optimized. In December 2023, the government issued Presidential Regulation Number 55 of 2023 and Minister of Finance Regulation Number 168 of 2023 to alter the payroll tax scheme and simplify the calculation procedures of Income Tax Article 21. Additionally, Director General of Taxes Regulation Number PER-2/PJ/2024 was issued to regulate changes in creating withholding evidence and reporting the periodic Income Tax Article 21/26 return. This paper aims to analyze the impact of the new payroll tax scheme on the tax burden for taxpayers, the new reporting scheme's effect on tax administration regarding ease of administration, and the obstacles in implementing these new schemes. This study is expected to offer useful recommendations for the government and other stakeholders in their efforts to continually improve the national tax system. The research method used is qualitative, with data collected from literature studies and case studies. The results show that changes in the calculation and reporting schemes of Income Tax Article 21/26, viewed from the principle of ease of administration, meet the criteria of convenience, certainty, efficiency, and simplicity. However, implementation faces several obstacles, including minimal time for socializing the regulatory changes, resistance to regulatory changes, technological limitations, and regulatory issues. The broader policy implications of the new payroll tax scheme for tax administration in Indonesia include increased administrative efficiency, better tax compliance, improved tax information systems, simplification of the tax reporting process, and impacts on workforce and salaries